Purchase Intention of Islamic Life Insurance among Online Motorcycle Taxi Drivers: A Technology Acceptance Model Approach - Affandi Al Imadi Hasibuan; Andri Soemitra; Tuti Anggraini (Fakultas Syariah IAIN Langsa, 2026)
Ideally, increased public awareness and the growing accessibility of digital technology should lead to higher interest in Islamic life insurance. However, in reality, the level of market penetration and purchase intention remains relatively low, particularly among online motorcycle taxi (ojek online) drivers, despite their high occupational risk. This study aims to examine the influence of trust, perceived usefulness, and perceived ease of use on the intention to purchase Islamic life insurance by applying the Technology Acceptance Model (TAM). A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) on data collected from online motorcycle taxi drivers. The findings reveal that trust and perceived ease of use have a positive and significant effect on purchase intention, while perceived usefulness also shows a positive effect, although with lower statistical significance. These results highlight that enhancing trust, simplifying service processes, and clearly communicating product benefits are critical factors in increasing the adoption of Islamic life insurance among informal sector workers.